Sewage sludge composting in a rotary drum reactor: stability and kinetic analysis - Ashish Kumar Nayak; Ajay S. Kalamdhad (International Journal of Recycling of Organic Waste in Agriculture)
Background Composting is one of the sustainable practices to convert sewage sludge into useful agricultural product because it is rich in organic matter, micro- and macronutrients, which is essential for plants growth and soil fauna to live. Therefore, the present study was to recycle the sewage sludge by rotary drum composter. Five sets of experiments (C/N 15, 20, 25, 30 including control) were carried out in the reactor, where sewage sludge was coupled with sawdust and cattle manure to attain the optimal feedstock. The process was monitored with respect to physico-chemical characteristics and stability parameters during 20 days of composting period. In addition, the kinetic parameters km and rm have been evaluated in the present work. Results Higher reductions in CO2 evolution and oxygen uptake rate (OUR) observed in C/N 30 showed the stability, resulting in the total biodegradable ingredients to be stabilized. Similarly, higher percentage reduction in carbon-nitrogen ratio was observed in C/N 30 followed by C/N 20, C/N 25, C/N 15 and control experiments, respectively, indicates maximum degradation was achieved; as it corroborate higher temperature regime occurred in C/N 30. The composting parameters such as moisture content, volatile solids, CO2 evolution, OUR and C/N ratio were reduced significantly (p.05). The kinetic model used illustrated the comparable variations in Michaelis constant (km) and maximum rate constant (rm) under varying proportions of the initial feedstock. The overall assessment of kinetic data for C/N 30 experiment showed enhancement of degradation during the composting process. Conclusions The results suggested that composting of sewage sludge with optimal proportion of cattle manure and saw dust, especially in C/N 30, can produce stable compost within 20 days of composting.